A novel 18F-labeled clickable substrate for targeted imaging of SNAP-tag expressing cells by PET in vivo. Issue 77 (7th September 2021) - Depke, Dominic Alexej; Konken, Christian Paul; Rösner, Lukas; Hermann, Sven; Schäfers, Michael; Rentmeister, Andrea
Abstract : In this work, high-contrast PET imaging of subcutaneous SNAP-tag expressing tumor xenografts is achieved by bioorthogonal covalent targeting with a novel 18 F-based radioligand in vivo . Abstract : Bioorthogonal covalent labeling with self-labeling enzymes like SNAP-tag bears a high potential for specific targeting of cells for imaging in vitro and also in vivo . To this end, fluorescent SNAP substrates have been established and used in microscopy and fluorescence imaging while radioactive substrates for the highly sensitive and whole-body positron emission tomography (PET) have been lacking. Here, we show for the first time successful and high-contrast PET imaging of subcutaneous SNAP-tag expressing tumor xenografts by bioorthogonal covalent targeting with a novel 18 F-based radioligand in vivo .